Improved lattice model for concrete fracture - Arslan, A; Ince, R; Karihaloo, BL (Asce-Amer Soc Civil Engineers, 2002)
An improved regular lattice network model is developed and validated for fracture of concrete structures. The improvements pertain to the inclusion of the tension softening response of the matrix phase, and of the modelling of structural response by incrementing C the deformation rather than the load. A further development is the use of a regular square rather than a triangular lattice network to speed up the computations. These improvements eliminate the need for the introduction of arbitrary scaling parameters in the beam element failure criteria. Validation checks on notched three-point bend concrete specimens confirm the predictive capabilities of the improved lattice model with regard to both the load-deformation behavior and the energy dissipation mechanisms.
Keywords: lattices; concrete; fractures; models